MODELLING THE INTEREST RATE ASYMMETRIC PASS-THROUGH IN TURKISH LOAN MARKET: NEW EVIDENCE FROM THRESHOLD COINTEGRATION ANALYSIS - Gülden BÖLÜK; Fatih DEMİR (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
ABSTRACT: The current study aims to examine the relationship between banks’ marginal cost (official policy rate) and retail rates in Turkish banking loan market. We tested asymmetric pass-through by using threshold autoregressive (TAR) and momentum threshold autoregressive (MTAR) and weekly data over the period of 2011:1 to 2021:36. Empirical results reveal that there is incomplete pass-through between policy rate and retail lending rates as vehicle, housing, and commercial loans. Moreover, it’s found that while housing and commercial loan rates are rigid downward, vehicle loan rates are rigid upward. The weak and incomplete adjustment indicate that contestability in Turkish banking market has worsened during the last decades. Within this context, positive, and negative asymmetries in transmission process of Turkish banking system imply that impact of central bank decision on macroeconomic variables (such as inflation, growth etc.) is accepted to be weak in Turkey. ÖZ: Bu çalışma, bankaların marjinal maliyeti (resmi politika oranı) ile perakende oranları arasındaki ilişkiyi Türkiye bankacılık kredi piyasası kapsamında analiz etmeyi amaçlamaktadır. Asimetrik geçişkenliği, eşik otoregresif (TAR) ve momentum eşik otoregresif (MTAR) modellerini ve 2011: 1-2021: 36 dönemi haftalık verileri kullanarak test ettik. Ampirik sonuçlar, politika faiz oranı ile taşıt, konut ve ticari kredilerden oluşan perakende kredi oranları arasında tamamlanamayan geçişkenlik olduğunu ortaya koymaktadır. Ayrıca konut ve ticari kredi oranlarının aşağı yönlü katı, araç kredisi oranlarının ise yukarı yönlü katı olduğu görülmüştür. Zayıf ve tamamlanamayan ayarlama, son on yılda Türk bankacılık piyasasındaki rekabet edilebilirliğin kötüleştiğini göstermektedir. Bu bağlamda, Türk bankacılık sisteminin aktarım sürecindeki pozitif ve negatif asimetriler, Türkiye'de merkez bankası kararlarının makroekonomik değişkenler (enflasyon, büyüme vb.) üzerindeki etkisinin zayıf olarak kabul edildiğini göstermektedir.